Analisis Penggunaan Gaya Bahasa dalam Buku Antologi Puisi 16 Penyair Memeluk Bumi - Paramita Susanti; Wahyuni Kusumadewi; Otin Otin (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Poetry is a type of literary work that expresses the emotions, ideas and contents of the poet's heart. Poetry usually expresses its contents using linguistic types. The aim of this research is to provide a detailed description of the language style used in the poetry anthology book 16 Poets Embrace the Earth. A qualitative descriptive approach was used. The book 16 Poets Hugging the Earth by Rayakultura was used as the data source. Data collection methods, including collecting and examining written data on poetry, were used to conduct data analysis. Data reduction is also used in processing the data to classify and identify the language styles contained in the poetry. The results of the research show that the poetry in the book 16 Poets Hugging the Earth contains several language styles, namely the group of comparative and contradictory language styles. The several language styles found in the poem aim to move society to prioritize caring for and protecting the environment.